Power scheduling of more electric aircraft power system - Lin, Yujing (2016)
In recent years, advance in more electric aircraft has brought numerous benefits including reducing the environmental impact brought by aviation industry. To further this effect, research in electric power system (EPS) has been done extensively to optimize power efficient and fuel consumption. Power scheduling plays a crucial role in this system and the management of load is the primary means for better optimization. For this project a power scheduling method is developed based on the EPS of Boeing 787. Different constraints are considered and the problem is formulated and simulated using MATLAB. The results demonstrate the efficiency of the algorithm during a stimulated 2 hour flight.